A novel trityl/acridine derivatization agent for analysis of thiols by (matrix-assisted)(nanowire-assisted)laser desorption/ionization and electrospray ionization mass spectrometry. Issue 45 (15th November 2017) - Topolyan, Artyom P.; Belyaeva, Maria A.; Slyundina, Mariya S.; Ilyushenkova, Valentina V.; Formanovsky, Andrey A.; Korshun, Vladimir A.; Borisov, Roman S.
Abstract : A new agent was used for fixed-charge derivatization of low molecular weight thiols. Abstract : The derivatization reagent was prepared in situ by the reaction of tris(2, 6-dimethoxyphenyl)methylium hexafluorophosphate with N -(2-aminoethyl)maleimide and used for the modification of a number of low molecular weight thiols. The adducts were analyzed by (MA)(NA)LDI MS and ESI MS. All registered mass spectra ((MA)(NA)LDI, ESI) revealed intense peaks of the cations of the derivatization products. The increment of the derivatization agent (499 Da) shifts the ion peaks of analytes from noisy low mass regions, thus allowing the detection of low molecular weight thiols. LDI analysis of the natural-gas condensate sample showed the presence of saturated alkylthiols (up to C22 H45 SH).